Health Care Resource Utilization and Associated Costs Among Metastatic Cutaneous Melanoma Patients Treated with Ipilimumab (INTUITION Study). (19th May 2017) - McArthur, Grant A.; Mohr, Peter; Ascierto, Paolo Antonio; Arance, Ana; Banos Hernaez, Ana; Kaskel, Peter; Weichenthal, Michael; Shinde, Reshma; Stevinson, Kendall
Abstract : Background: There are limited real‐world data on health care resource utilization (HCRU) among advanced melanoma patients. The objective of this study was to describe HCRU and health care costs associated with the management of advanced melanoma patients receiving ipilimumab. Methods: This retrospective multinational, observational study included advanced melanoma patients from Australia, Germany, Italy, and Spain who had received at least 1 dose of ipilimumab. Data extracted from medical charts included inpatient admissions, outpatient visits, surgical procedures, laboratory investigations, radiation therapy, imaging studies, and concomitant medications. Cost estimates were based on unit costs from country‐specific standard reimbursement sources. Subgroup analyses were performed for BRAF mutation status and ipilimumab refractory patients, who had disease progression within 24 weeks of their last dose of ipilimumab. Results: Mean age of 362 enrolled patients was 60.6 years (standard deviation [SD] 14.4). During a median follow‐up period of 30.2 weeks, 57% of patients were admitted to hospital and 16% underwent surgery. Health care resource utilization rates varied substantially across countries and were highest in Germany. Concomitant medications to treat adverse events were commonly used. Subgroup analyses showed higher utilization rates among ipilimumab refractory and BRAF mutant patients. Mean weekly total costs associated with HCRU were lower in the pre‐progression period (€107; 95% confidence interval (CI): 79–145) than in the post‐progression period (€216; 95% CI: 180–259). Conclusion: Health care resource utilization pattern and associated costs among patients treated with ipilimumab varied greatly among countries and between pre‐ and post‐progression periods. There is a high economic burden associated with ipilimumab refractory melanoma. Abstract : The objective of this study was to describe health care resource utilization and health care costs associated with the management of advanced melanoma patients receiving ipilimumab.